Observation of O+ (4P-4D0) lines in electron aurora over Svalbard - N. Ivchenko (Annales Geophysicae, 2004)
This work reports on observations of O+ lines in aurora over Svalbard, Norway. The Spectrographic Imaging Facility measures auroral spectra in three wavelength intervals (Hβ, N+2 1N(0,2) and N+2 1N(1,3)). The oxygen ion multiplet (4639-4696Å) is blended with the band. It is found that in electron aurora, the brightness of this multiplet, is on average, about 0.1 of the total brightness. A joint optical and incoherent scatter radar study of an electron aurora event shows that the ratio is enhanced when the ionisation in the upper E-layer (140-190km) is significant with respect to the E-layer peak below 130km. Rayed arcs were observed on one such occasion, whereas on other occasions the auroral intensity was below the threshold of the imager. A one-dimensional electron transport model is used to estimate the cross section for production of the multiplet in electron collisions, yielding 0.18x10-18cm2.